Anticancer immunotherapy by CTLA-4 blockade: obligatory contribution of IL-2 receptors and negative prognostic impact of soluble CD25 - Hannani, Dalil; Jäger, Dirk (Cell research, 2015)
The cytotoxic T lymphocyte antigen-4 (CTLA-4)-blocking antibody ipilimumab induces immune-mediated long-term control of metastatic melanoma in a fraction of patients. Although ipilimumab undoubtedly exerts its therapeutic effects via immunostimulation, thus far clinically useful, immunologically relevant biomarkers that predict treatment efficiency have been elusive. Here, we show that neutralization of IL-2 or blocking the α and β subunits of the IL-2 receptor (CD25 and CD122, respectively) abolished the antitumor effects and the accompanying improvement of the ratio of intratumoral T effector versus regulatory cells (Tregs), which were otherwise induced by CTLA-4 blockade in preclinical mouse models. CTLA-4 blockade led to the reduction of a suppressive CD4(+) T cell subset expressing Lag3, ICOS, IL-10 and Egr2 with a concomitant rise in IL-2-producing effector cells that lost FoxP3 expression and accumulated in regressing tumors. While recombinant IL-2 improved the therapeutic efficacy of CTLA-4 blockade, the decoy IL-2 receptor α (IL-2Rα, sCD25) inhibited the anticancer effects of CTLA-4 blockade. In 262 metastatic melanoma patients receiving ipilimumab, baseline serum concentrations of sCD25 represented an independent indicator of overall survival, with high levels predicting resistance to therapy. Altogether, these results unravel a role for IL-2 and IL-2 receptors in the anticancer activity of CTLA-4 blockade. Importantly, our study provides the first immunologically relevant biomarker, namely elevated serum sCD25, that predicts resistance to CTLA-4 blockade in patients with melanoma.